First fossil record of Ischaliidae Blair, 1920 (Coleoptera) from Eocene Baltic amber - Alekseev, Vitalii I.; Telnov, Dmitry (Zootaxa, 2016)
Ischalia Pascoe, 1860, the monotypic genus of Ischaliidae, was placed as a subfamily among Pyrochroidae or Anthicidae by earlier authors. Nikitsky (1992) raised the status of Ischaliidae to the family rank. This position has been largely accepted and consequently followed by recent authors dealing with Ischalia, as well as in our paper. Ischaliidae is known from the Palaearctic (the Himalayas, East Asia: easternmost Russia, Japan, E China), South East Asia (southwards to Java, Borneo and the Philippines), and the Nearctic region (southern Canada, U.S.A.). No recent European representatives of Ischalia are known. At present, this genus is composed of 43 species worldwide (Gusakov & Telnov 2007; Saitô 2011; Young 2011; Young 2014; Saitô & Young 2015) placed in three subgenera (Young 2011): Ischalia s. str.—37 species, Eupleurida LeConte, 1862—5 species, Nitidischalia Young, 2011—1 species. Ischaliidae is most diverse in tropical rainforests, but many species are also known from subtropical to temperate zones. Adults and larvae of two Nearctic Ischalia feed on fungal mycelium growing on decaying wood of coniferous and broad-leaved trees (e.g. Pinus ponderosa, Lithocarpus densiflora) (Young 1985). Mimicry has been described among Bornean Ischaliidae, Tenebrionidae and Chrysomelidae (Telnov 2005) and also among Ischaliidae, Omalisidae, Lycidae and Endomychidae (Kazantsev & Young 2010).